Alternative activation of macrophages by IL-4 requires SHIP degradation - Weisser, Shelley B. (Eur J Immunol, 2011)
Alternatively activated macrophages are critical in host defense against parasites and are protective in inflammatory bowel disease, but contribute to pathology in asthma and solid tumors. The mechanisms underlying alternative activation of macrophages are only partially understood and little is known about their amenability to manipulation in pathophysiological conditions. Herein, we demonstrate that Src homology 2-domain-containing inositol-5′-phosphatase (SHIP)-deficient murine macrophages are more sensitive to IL-4-mediated skewing to an alternatively activated phenotype. Moreover, SHIP levels are decreased in macrophages treated with IL-4 and in murine GM-CSF-derived and tumor-associated macrophages. Loss of SHIP and induction of alternatively activated macrophage markers, Ym1 and arginase I (argI), were dependent on phosphatidylinositol 3-kinase (PI3K) activity and argI induction was dependent on the class IA PI3Kp110δ isoform. STAT6 was required to reduce SHIP protein levels, but reduced SHIP levels did not increase STAT6 phosphorylation. STAT6 transcription was inhibited by PI3K inhibitors and enhanced when SHIP was reduced using siRNA. Importantly, reducing SHIP levels enhanced, whereas SHIP overexpression or blocking SHIP degradation reduced, IL-4-induced argI activity. These findings identify SHIP and the PI3K pathway as critical regulators of alternative macrophage activation and SHIP as a target for manipulation in diseases where macrophage phenotype contributes to pathology.